PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN EKOWISATA PADA KAWASAN TAMAN WISATA ALAM TANJUNG BELIMBING KECAMATAN PALOH KABUPATEN SAMBAS - Elisca, Elisca; Idham, M; M, Iskandar A (Universitas Tanjungpura, 2020)
Paloh is a coastal area that has the potential to apply the concept of community-based ecotourism. Tanjung Belimbing Nature Tourism Park is a Nature Tourism Park area that has a beautiful natural panorama with the potential of plants and wildlife that attracts tourists, making the community develop into an area that is needed for the development of the area as an ecotourism area. The research objective is to discuss the level of community participation in the development of the Tanjung Belimbing TWA region as an ecotourism area and also the factors that influence the low level of the community in the process of regional development. The research method uses survey method, through purposive sampling technique with the help of a questionnaire as a research instrument. The results showed the level of community participation (28.89%) was classified as high participation rate, (13.33%) moderate participation rate, and (57.78%) with low participation rate. Based on the level of participation expressed by Arnstein Participation in the level of participation of the people of Sebubus Village only reached the level of participation Consultation in this familyKeywords: Community, Ecotourism, Nature Tourism Parks, Participation